Unveiling the Therapeutic Potential of Systemic Ozone on Skin Wound Repair: Clinical, Histological, and Immunohistochemical Study in Rats - De Medeiros Cardoso, Jânderson; Ervolino, Edilson [UNESP]; Miyasawa, Erton Massamitsu; Theodoro, Leticia Helena [UNESP]; Padovan, Luis Eduardo Marques; Pereira, Estevão Lopes [UNESP]; De Molon, Rafael Scaf [UNESP]; Garcia, Valdir Gouveia (Wiley, 2024)
This study sought to examine the effects of systemic ozone (O3) treatment on the healing of skin wounds induced on the dorsal surface of Wistar rats. The skin wounds were created using a 10 mm round punch following the sagittal medial plane in 72 rats. Then, the animals were randomly assigned to four groups, each receiving the following treatments: group C, which did not undergo treatment with the O3/O2 mixture; group OZ0.3, administered the O3/O2 mixture at a dose of 0.3 mg/kg; group OZ0.7, given the O3/O2 mixture at a dose of 0.7 mg/kg; and group OZ1.0, provided with the O3/O2 mixture at a dose of 1.0 mg/kg. Six animals from each group were euthanized at 7, 14, and 21 days postoperatively. Clinical, histological, histometric, and immunohistochemical (IHC) analyses were accomplished. Data from clinical and histometric assessments revealed that OZ0.7 and OZ1.0 demonstrated more favorable healing, with greater wound contraction observed in the OZ1.0 group at 14 and 21 days. Histologically, the OZ1.0 group exhibited aspects consistent with an accelerated tissue repair process. IHC analysis revealed greater vascular endothelial growth factor (VEGF) immunostaining in the OZ0.7 (7 days) and OZ1.0 (7 and 14 days) groups compared to the C group. Expression of transforming growth factor beta-1 was significantly increased in the OZ0.7 (14 days) and OZ1.0 (7 and 14 days) groups compared to the C group. In conclusion, our data suggest that systemic use of O3 enhanced tissue repair in cutaneous wounds in a dose-dependent manner, with concentrations of 1.0 mg/kg providing the most beneficial effects. Furthermore, the results of this study implicate the use of O3 for the treatment of skin wounds aiming at improving the healing process over time. Our findings suggest the use of O3 as a viable alternative to enhance wound healing and repair.